(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The paper focus on some examples of autonomous movements (“alter-globalist”, social) in Slovenia during the 2000sthat involved the “aesthetics” in conducting their political activity. At the same time, the essay questions ‘politicized’ artistic events, that is, those events that can be understood as belonging to the world of art, because they were created by artists or because they declare themselves artistic. Based on the analysed examples of artivistic performances, the author explains that artivism is a kind of public interventionism which hybrid nature enables quick passages from the pre- dominantly artistic into the predominantly political sphere and back.